Investigating the influence of homebuyers’ sociodemographic factors on preferences of sustainable affordable housing - Lai, Li Xuan; Wong, Phui Fung; Yong, Felicia Yan Yan (International Journal of Strategic Property Management, 2023)
Low- and middle-income groups face difficulties in homeownership because of the urbanisation and rising living standards, in which they rely heavily on the government’s housing provision. Yet, affordable housing provided in Malaysia has been repeatedly criticised as it is not up to homebuyers’ expectations and is not supported to reach sustainable goals. Hence, this research aims to investigate the influence of the sociodemographic background of the homebuyers on their preferences for sustainable affordable housing in Malaysia. The questionnaire was designed and responses were obtained from 316 low- and middle-income homebuyers. Spearman rank correlation and ordinal regression were used to investigate the association between homebuyers’ sociodemographic characteristics and their preference for sustainable affordable housing. Spearman correlation analysis revealed that gender, generation, marital status and monthly income were significantly correlated with sustainability criteria. The ordinal regression model reflected that stronger preferences for sustainable affordable housing were shown among female homebuyers, Gen Y and Baby Boomer homebuyers and married ones. The research findings close the gap between users (homebuyers) and the providers (developer/government) in the provision of affordable housing. Developers and the local authorities can provide sustainable affordable housing solutions that suit the needs of different homebuyers.